Cutting confidential : true confessions and trade secrets of a celebrity hairdresser - Lockes, Shaun (Orion Books, 2007)
Hairdressers have become an extension of our social circle; we talk to them for hours, we tell them things we wouldn't tell our closest friends and when they ask, 'trust me' we invariably do. In this expose on the hairdressing industry we accompany the famous Mane Man on his travels around London. Dashing from a TV make-over show to a glamorous fashion launch, Mane's work is photographed, papped and featured on the front of magazines across the world. There are drugs, there are egos and there are flirtations. But more than anything, there's a lot of plain talking, razor-sharp humour and more hairspray than an up-do in a gale. Mane's appointment book is always full and the reader is invited along to enjoy, to laugh and to learn hair secrets.